2020
DOI: 10.1002/adhm.202001414
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Biomaterials for Bone Regenerative Engineering: A Comprehensive Review of the Field and Considerations Regarding Biocompatibility and Biodegradation

Abstract: Graphene and its derivatives have continued to garner worldwide interest due to their unique characteristics. Having expanded into biomedical applications, there have been efforts to employ their exceptional properties for the regeneration of different tissues, particularly bone. This article presents a comprehensive review on the usage of graphene‐based materials for bone regenerative engineering. The graphene family of materials (GFMs) are used either alone or in combination with other biomaterials in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 228 publications
0
50
0
Order By: Relevance
“…The presence of the high-modulus GFMs in low-modulus polymer matrices can lead to significant reinforcements in the mechanical properties of composite structures. The reinforcing effects of the GFMs in polymer matrices is governed by the structure of the graphenic material in use, the polymer matrix, the composite preparation method, and the dispersion of the graphenic filler within the matrix and their interactions 27 , 59 . In 3D printed scaffolds specifically, in addition to the structural and physicochemical properties of the composite materials, geometrical features such as pore size, pore area, and strand diameter play important roles 50 , 60 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the high-modulus GFMs in low-modulus polymer matrices can lead to significant reinforcements in the mechanical properties of composite structures. The reinforcing effects of the GFMs in polymer matrices is governed by the structure of the graphenic material in use, the polymer matrix, the composite preparation method, and the dispersion of the graphenic filler within the matrix and their interactions 27 , 59 . In 3D printed scaffolds specifically, in addition to the structural and physicochemical properties of the composite materials, geometrical features such as pore size, pore area, and strand diameter play important roles 50 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…The biocompatibility of the GFMs is regulated by their physicochemical characteristics (size, shape, surface chemistry), exposure conditions (medium, dose, duration), and the cell type 25,27 . Most studies have shown that the incorporation of small amounts of the GFMs into scaffolds helps to improve their biological performance [67][68][69] .…”
Section: Mechanical Evaluation Of the 3d Printed Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different approaches have been utilized for bone tissue engineering (BTE); the most common were those that tried to mimic the natural process of bone repair using 3D osteoconductive scaffolds. Recently, the potential of GOBMs has gained tremendous attention to facilitate and improve BTE [ 54 , 55 , 56 , 57 , 58 , 59 ] in its various forms, namely scaffolds, coatings, guided bone membranes, and drug delivery systems [ 60 ]. Moreover, GOBMs, particularly with low oxygen contents, have a pivotal influence on adult mesenchymal stem cells (MSCs) to increase osteoinductivity and osteoconductivity [ 11 , 61 ].…”
Section: Development Of Tissues and Organs Using Graphene-based Materialsmentioning
confidence: 99%
“…Recently, it was shown that the application of graphene as a filler can improve the mechanical properties of polymer materials [ 20 , 21 ]. The use of graphene derivatives such as graphene oxide (GO) or reduced graphene oxide (rGO), which contain hydroxylic and carboxylic groups, can also improve the interaction of composites with cells and biomolecules and enhance cell growth, cell differentiation and cell proliferation [ 22 , 23 ]. At the same time, GO and rGO similar to graphene enhances the mechanical properties of polymer materials [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%